STRUKTUR DAN KOMPOSISI VEGETASI POHON SERTA ESTIMASI BIOMASSA, KANDUNGAN KARBON DAN LAJU FOTOSINTESIS DI TAMAN NASIONAL GUNUNG HALIMUN-SALAK - Muhammad Mansur; Nuril Hidayati; Titi Juhaeti (Jurnal Teknologi Lingkungan, 2011)
Research the structure and composition of vegetation, biomass estimation, carbon content and the rate of photosynthesis was conducted in Citalahab Central Village,Gunung Halimun-Salak National Park, West Java, on August 2010. The purpose of research to determine the components and characteristics of each tree species at the study sites associated with biomass, the rate of CO2 assimilation and transpiration. Results showed that, the form of classified forest area of primary forest with a little disturbed. There were recorded 337 individual trees (stem diameter > 10 cm) per hectare from 71 species, 50 genera and 32 families. Lauraceae, Fagaceae, Myrtaceae, Rubiaceae and Meliaceae are the 5 most common families found in the plot area, thatis dominated by Altingia excelsa, Blumeodendron elateriospermum, Ardisia zollingeri, Gordonia excelsa, Tricalysia singularis, Castanopsis acuminatissima, Knema cinerea, Laportea stimulant, Vernonia arborea and Dysoxylum excelsum. Estimated biomass recorded of 304.5 tons dry weight / ha with a carbon content of 152.3 tons / ha of basal area of 28.89 m2/ha. Quercus oidocarpa, Litsea noronhae, Saurauia nudiflora, Castanopsis argentea and Altingia excelsa has recorded the highest photosyntheticrates compared with other species. While the highest transpiration rate is owned by the Macaranga triloba, Sandoricum koetjape, Prunus arborea, Urophyllum corymbosum and Altingia excelsa.